A transient expression system to assay putative antifungal genes on powdery mildew infected barley leaves - Nielsen, K.; Olsen, O.; Oliver, Richard (1999)
A transient expression system has been established to assay the regulation and impact of putative antifungal proteins at the single cell level in barley (Hordeum vulgareL.) epidermal leaf cells infected with powdery mildew (Erysiphe graminisf.sp.hordei).The system combines biolistic transformation with direct comparison of the fungal attack in transfected and wild type cells. Many epidermal cells showed detectable expression of marker genes including a novel improved version of green fluorescent protein (GFP). The marker was detectable for at least 10 days during which individual host cells supported an unaffected asexual life-cycle of the pathogen.